Calling songs and duets of two new species in the Amblycorypha rotundifolia complex (Tettigoniidae, Phaneropterinae) - Timothy G. Forrest; Jennifer A. Hamel; C. Tate Holbrook (Journal of Orthoptera Research)
Two new species in the rotundifolia complex of Amblycorypha from the southern Appalachian Mountains of the USA are described. The calling songs and duets of these two phaneropterine katydids are characterized and discussed. Unlike other members of the rotundifolia complex, Amblycorypha zipticka sp. nov. and A. monticola sp. nov. have multicomponent calling songs. The songs of Amblycorypha zipticka sp. nov. have two syllable types that differ in their rates with temperature (1.5/s and 3.8/s at 25oC). Male A. monticola sp. nov. emit syllables that are grouped into regular echemes. Syllable and echeme rates are temperature dependent. Syllable rates of A. monticola sp. nov. are the fastest in the rotundifolia complex (45/s at 25°C). While calling, males of both species produce ticks that resemble the tick responses of females during duets. As predicted, the timing of the males’ ticks within their songs occurs when female replies are expected, and their timing does not change when they call alone or in duets with females. These findings are discussed regarding acoustic countermeasures to competitor eavesdropping and the evolution of signal complexity in the phaneropterines.